Logical thinking performance in different levels of Malaysian autistic children - Joari, Robi'atul 'Adawiyah; Chin, Ai Vee; Abd Manaf, F.; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The aim of this study was to examine the overall performance of different levels of autistic children aged from 4- 8 years on a logical thinking test in the Malaysian context. The study was conducted at the National Autism Society of Malaysia (NASOM) center in Klang Lama. The instrument used in this study is the Logical Operations and Conservation (LOC) test developed by by Vianello and Marin (1997). ANOVA was used to compare the mean of LOC score and autism levels among the participants. The results revealed that there is a significant difference between LOC score and autism levels among the participants (F (2,26) =11.449, p=0.000). There is no significant difference between male (M=3.7500; SD = 3.7500) and female (M=3.7500; SD = 8.66025 children). This signifies that logical thinking ability among autistic children is not affected by their gender. The discussions and suggestions are discussed further in the article.